Exogenous 6-Benzyladenine Improves Waterlogging Tolerance in Maize Seedlings by Mitigating Oxidative Stress and Upregulating the Ascorbate-Glutathione Cycle - Wang, Ji; Wang, Daye; Zhu, Min; Li, Fenghai (Frontiers in Plant Science, 2021)
The synthetic cytokinin 6-benzyladenine (6-BA) regulates plant growth and prevents the negative consequences of various forms of abiotic stress, including waterlogging in crop plants. The present study aimed to investigate the effects of exogenous 6-BA on the growth, oxidative stress, and ascorbate-glutathione (AsA-GSH) cycle system in the inbred SY-MY13 (waterlogging-resistant) and SY-XT1 (waterlogging-sensitive) seedlings of waxy corn in conditions of waterlogging stress. The results demonstrated that waterlogging stress causes chlorosis and necrosis in waxy corn leaves, inhibiting growth and leading to the accumulation of reactive oxygen species (ROS), which induces oxidative stress and, in turn, reduces membrane lipid peroxidation and the disruption of membrane homeostasis. This is specifically manifested in the increased concentrations of superoxide anion radicals (O2-), hydrogen peroxide (H2O2), and malondialdehyde (MDA), in addition to increased relative electrical conductivity (REC%) values. The SY-MY13 strain exhibited growth superior to that of SY-XT1 when waterlogged due to its excellent waterlogging resistance. Thus, exogenous 6-BA was found to be effective in enhancing the growth of plants stressed by waterlogging in terms of the weight of the shoots and roots, shoot height, and leaf area. In addition to this, exogenous 6-BA also reduced the accumulation of O2-, H2O2, and MDA, increased ascorbate peroxidase (APX), glutathione reductase (GR), dehydroascorbate reductase (DHAR), and monodehydroascorbate reductase (MDHAR) activity, and enhanced ascorbic acid (AsA), and reduced glutathione (GSH) concentration through the regulation of the efficiency of the AsA-GSH cycle system in maize plants. Hence, the application of exogenous 6-BA can alleviate waterlogging-induced damage and improve waterlogging tolerance in waxy corn via the activation of the AsA-GSH cycle system and the elimination of ROS.